Multidisciplinary Discussion for Fibrotic Hypersensitivity Pneumonitis with a Positive Antigen Avoidance - Okuda R; Takemura T; Misumi T; Hagiwara E; Ogura T (Journal of Asthma and Allergy, 2023)
Ryo Okuda,1 Tamiko Takemura,2 Toshihiro Misumi,3 Eri Hagiwara,1 Takashi Ogura1 1Department of Respiratory Medicine, Kanagawa Cardiovascular and Respiratory Center, Yokohama, Japan; 2Department of Pathology, Kanagawa Cardiovascular and Respiratory Center, Yokohama, Japan; 3Department of Data Science, National Cancer Center Hospital East, Chiba, JapanCorrespondence: Ryo Okuda, Department of Respiratory Medicine, Kanagawa Cardiovascular and Respiratory Center, 6-16-1 Tomioka-higashi, Kanazawa-ku, Yokohama, Japan, Tel +81-45-701-9581, Email b980013@yahoo.co.jpBackground: In the two fibrotic hypersensitivity pneumonitis (fHP) diagnostic guidelines, the multidisciplinary discussion (MDD) is required to be performed in diagnosis of fHP, as in idiopathic pulmonary fibrosis (IPF) diagnostic guideline. Although some patients with fHP can improve disease condition during antigen avoidance, which can facilitate the diagnosis of fHP, it is unclear if MDD is necessary in all patients with suspected fHP who improved an antigen avoidance.Objective: To investigate the diagnosis of fHP via MDD with positive antigen avoidance tests (AATs) and the clinical diagnosis with positive AATs.Methods: A single-center, retrospective study was conducted. Between 2012 and 2019, patients with fHP were enrolled in the study. Patients in the MDD diagnostic group consisted of patients diagnosed with MDD, including histopathology findings and positive ATTs, and patients in the clinical diagnostic group were diagnosed by two respiratory physicians and had positive ATTs.Results: AAT was performed on 72 of 219 patients, and 58 had positive AATs. The study included 37 patients in the MDD diagnosis group and 21 patients in the clinical diagnosis group. No significant differences in overall survival (OS) were detected between the two groups (HR: 1.99 [95% CI: 0.82‒4.83], p = 0.127). The conducting MDD was not a risk factor for OS; only < 79% forced vital capacity was a risk factor in the multivariate Cox hazard regression analysis. No significant difference in annual changes of forced vital capacity, diffusion of the lung for carbon monoxide and Krebs von den Lungen-6 between the MDD diagnostic and the clinical diagnostic groups were observed (p = 0.41, 0.79, and 0.81, respectively).Conclusion: In patients with positive AATs, the disease progression of the MDD diagnostic and the clinical diagnostic groups were similar. Therefore, MDD could not be necessary in all patients with suspected fHP who had positive AATs.Keywords: chronic hypersensitivity pneumonitis, diagnostic method, hypersensitivity pneumonitis, multidisciplinary team, subacute hypersensitivity pneumonitis